Before and after the global crisis - "Mohan, T.T.Ram" (New Delhi, 2013)
it is nearly six years since the global economic crisis erupted. The crisis has stretched out for longer than most people had thought. The downturn in some parts of the world, notably Europe, has turned out to be more severe than expected.
Keywords: "Bank and banking, Economic policy"